Nicotine Modulates Mitochondrial Dynamics in Hippocampal Neurons - Godoy, Juan A. (2018)
Mitochondria are widely recognized as fundamental organelles for cellular physiology and constitute the main energy source for different cellular processes. The location, morphology, and interactions of mitochondria with other organelles, such as the endoplasmic reticulum (ER), have emerged as critical events capable of determining cellular fate. Mitochondria-related functions have proven particularly relevant in neurons; mitochondria are necessary for proper neuronal morphogenesis and the highly energy-demanding synaptic transmission process. Mitochondrial health depends on balanced fusion-fission events, termed mitochondrial dynamics, to repair damaged organelles and/or improve the quality of mitochondrial function, ATP production, calcium homeostasis, and apoptosis, which represent some mitochondrial functions closely related to mitochondrial dynamics. Several neurodegenerative disorders, such as Alzheimer’s, Parkinson’s, and Huntington’s diseases, have been correlated with severe mitochondrial dysfunction. In this regard, nicotine, which has been associated with relevant neuroprotective effects mainly through activation of the nicotinic acetylcholine receptor (nAChR), exerts its effects at least in part by acting directly on mitochondrial physiology and morphology. Additionally, a recent description of mitochondrial nAChR localization suggests a nicotine-dependent mitochondrial function. In the present work, we evaluated in cultured hipocampal neurons the effects of nicotine on mitochondrial dynamics by assessing mitochondrial morphology, membrane potential, as well as interactions between mitochondria, cytoskeleton and IP3R, levels of the cofactor PGC-1α, and fission-fusion-related proteins. Our results suggest that nicotine modulates mitochondrial dynamics and influences mitochondrial association from microtubules, increasing IP3 receptor clustering showing modulation between mitochondria-ER communications, together with the increase of mitochondrial biogenesis.